Prognoza korzyści dla społeczności i gmin Gubin oraz Brody z zagospodarowania złoża węgla brunatnego Gubin = Prognosis of economic benefits resulting from the planned mining and energy investment for the community and for Gubin and Brody municipalities - Uberman, Ryszard; Naworyta, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Construction of a new lignite mine, like the planned open-pit mine located on Gubin lignite deposit, is an investment that in society's reception is highly controversial. The local community's fears are related to relocation from the deposit's area, reconstruction of the infrastructure and alteration of previous functions of the land.
Keywords: korzyści ekonomiczne; kopalnie węgla brunatnego; złoże Gubin; economic benefits; lignite mine; Gubin deposit